2003
DOI: 10.1074/jbc.m211005200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Studies on Native and Mutated Forms of Perilipins

Abstract: Perilipin A coats the lipid storage droplets in adipocytes and is polyphosphorylated by protein kinase A (PKA); the fact that PKA activates lipolysis in adipocytes suggests a role for perilipins in this process. To assess whether perilipins participate directly in PKAmediated lipolysis, we have expressed constructs coding for native and mutated forms of the two major splice variants of the perilipin gene, perilipins A and B, in Chinese hamster ovary fibroblasts. Perilipins localize to lipid droplet surfaces an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
111
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(116 citation statements)
references
References 31 publications
(32 reference statements)
5
111
0
Order By: Relevance
“…The perilipin B cDNA subcloned into the pSR␣MSVtkneo retroviral expression vector (15) was kindly provided to us by Dr. John Tansey (Otterbein College, Westerville, OH). Ecotropic retroviral stocks were produced in transfected 293T cells as described previously (26), and used to infect cultured 3T3-L1 preadipocytes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The perilipin B cDNA subcloned into the pSR␣MSVtkneo retroviral expression vector (15) was kindly provided to us by Dr. John Tansey (Otterbein College, Westerville, OH). Ecotropic retroviral stocks were produced in transfected 293T cells as described previously (26), and used to infect cultured 3T3-L1 preadipocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in perilipin knockout mice have established an important role for perilipins in regulating lipolysis in adipocytes, and hence, controlling the mass of triacylglycerol deposited in adipose tissue (10, 11). The mechanisms by which perilipins maintain control of adipocyte triacylglycerol metabolism are poorly understood, although recent mutagenesis studies have identified structural motifs important to perilipin function in triacylglycerol storage and lipolysis (12)(13)(14)(15)(16)). An attractive model consistent with these data suggests that perilipins restrict the access of cytosolic lipases to triacylglycerol stored within lipid droplets, and thus suppress the rate of basal lipolysis under conditions when triacylglycerol storage is favored.…”
mentioning
confidence: 99%
“…This view, however, has recently been challenged by the following observations: 1) HSL-deficient mice are not obese, suggesting significant activity of lipase(s) other than HSL (10,12,19); 2) adipocytes derived from epididymal fat pads or embryonic fibroblasts of HSL null mice retain 50% of basal TAG lipase activity and are responsive to PKA activation (10,11,12,19); and 3) cell lines lacking endogenous HSL, i.e. 3T3-L1 preadipocytes (21), NIH 3T3 fibroblasts (22), and Chinese hamster ovary cells (23), exhibit significant TAG hydrolysis under basal and PKA-stimulated conditions. Thus, both HSL and non-HSL(s) play important roles in basal and PKA-stimulated lipolysis.…”
mentioning
confidence: 99%
“…1). Under nonstimulated (basal) conditions, Peri A acts as a barrier to HSL (22) and non-HSL(s) (21)(22)(23), thereby decreasing basal lipolysis (22,23) and increasing intracellular (TAG) storage (21,22). Upon lipolytic stimulation, Peri A is phosphorylated at up to six sites by PKA (25,28) (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation